An ultra-low Pd loading nanocatalyst with efficient catalytic activity1. Issue 12 (28th March 2015) - Jin, Yunxia; Xi, Jiangbo; Zhang, Zheye; Xiao, Junwu; Xiao, Fei; Qian, Lihua; Wang, Shuai
<x xml:space="preserve">Abstract</x> An ultra-low Pd loading nanocatalyst is synthesized by a convenient solution route of photochemical reduction and aqueous chemical growth.